Post-Prime Football Player Valuations: Depreciation Difference Between the English Premier League and the Top European Leagues - James Liu (International Journal of Financial Studies)
This study explores market value depreciation among soccer players across the top five European leagues, addressing a critical gap in the sports finance literature by focusing on post-prime valuation dynamics. Leveraging a dataset from the 2023/2024 season, player market values and attributes sourced from Transfermarkt and Sportmonks were analyzed using league-specific multilinear regression models. The findings reveal a consistent decline in market values beginning at age 27, with notable variation across leagues. The German Bundesliga demonstrates the steepest depreciation rates, suggesting shorter career peaks or distinct market dynamics. In contrast, the Italian Serie A and Spanish La Liga exhibit the slowest depreciation rates, preserving player value for older athletes longer than other leagues. The English Premier League and French Ligue 1 show moderate depreciation, with the Premier League’s decline closely aligning with Ligue 1 and diverging less from other leagues than traditionally assumed. These results challenge preconceived narratives about league-specific player valuations and offer empirical insights into the transfer market. By providing a nuanced understanding of depreciation trends, this study can inform strategic decisions for agents, managers, and clubs, particularly in optimizing contract negotiations, transfer strategies, and long-term asset management in professional football.